Legal and regulatory issues in Islamic banking: a Sri Lankan experience - Nafees, Seeni Mohamed; Ahmad, Muhamad Hassan; Masum, Ahmad; Md Nor, Mohd Zakhiri (Serials Publications (P) Ltd., 2018)
At the heart of every robust economy is a sound banking system which is ensured when an improved and standard legal system is in place. Sri Lanka is one of the non-Muslim countries that have legislation conducive to some extent for the operation of the Islamic banking. However, there are a number of hurdles for the development of Islamic banking. Therefore, this paper strives to examine selected legal and regulatory issues in Sri Lanka where Islamic banking is operated since 1997. The study found that although Islamic banking is successfully carried out to a certain extent, there are many identifiable legal and regulatory issues that have to be addressed in due course so as to push the industry to go forward more successfully and rapidly.